Diskurzní konektor »což« v neformálních mluvených rozhovorech - BÍLKOVÁ, Jana (Bohemistyka, 2021)
The artical presents the results of the corpus research focused on the function of expression což in informal spoken Czech. This word has the reference function, both in written and spoken texts. In terms of parts of speech classification, this word has mostly the status of the relative pronoun. In spoken conversation, however, there is an even greater difference between the frequency of the basic case form (což) and the other (čehož, čemuž, čemž, čímž). The high frequency of the word což in spoken Czech, as well as the dominance of its basic case form, can be caused by its frequent use as an uninflected discourse connective.